2019
DOI: 10.1186/s12911-019-0886-9
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ willingness to share digital health and non-health data for research: a cross-sectional study

Abstract: Background Patients generate large amounts of digital data through devices, social media applications, and other online activities. Little is known about patients’ perception of the data they generate online and its relatedness to health, their willingness to share data for research, and their preferences regarding data use. Methods Patients at an academic urban emergency department were asked if they would donate any of 19 different types of data to health researchers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 26 publications
(16 reference statements)
4
42
0
Order By: Relevance
“…The potential to glean such personal information about individuals when they might visit the hospital from social media reveal challenges associated with addressing several ethical and privacy concerns. Research has found that a large proportion of patients are willing to securely share their personal data sources 24 and are open to linking it to their electronic health record 22 for research purposes. In this type of work, privacy is of central importance.…”
Section: Discussionmentioning
confidence: 99%
“…The potential to glean such personal information about individuals when they might visit the hospital from social media reveal challenges associated with addressing several ethical and privacy concerns. Research has found that a large proportion of patients are willing to securely share their personal data sources 24 and are open to linking it to their electronic health record 22 for research purposes. In this type of work, privacy is of central importance.…”
Section: Discussionmentioning
confidence: 99%
“…mHealth applications can have a significant impact aiming to empower patients further. Numerous studies found that individuals are willing to share their medical data with respective healthcare providers to get a more suitable treatment [42,43]. Here we presented two strategies to ensure fast and secure communication between patients and healthcare providers based on established concepts, thereby providing intra-sectoral empowerment of involved parties.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to psychotic disorders and most relevant to our context, based on semistructured interviews with 112 psychotic disorder patients, in a work by Birnbaum et al [ 33 ], 80.7% (88/109) of patients were open to sharing their social media data with clinical researchers to explore how it can potentially inform their treatment. Drawing on these findings, and because clinical researchers have advocated that it is important to first focus on issues related to the accuracy, interpretability, meaning, and actionability of these data such as social media [ 34 ], in this paper, we focus on co-design exercises with clinicians. Our rationale is further bolstered by Baier’s [ 35 ] observation, “Without judicious consideration, social media use by [clinicians] can lead to inadvertent self-disclosures to [patients] that risk damaging the therapeutic alliance, interfering with therapeutic processes, and placing both the [patient] and clinician at risk”.…”
Section: Methodsmentioning
confidence: 99%